2023
DOI: 10.1002/dmrr.3726
|View full text |Cite
|
Sign up to set email alerts
|

Association of stress hyperglycemia ratio with in‐hospital new‐onset atrial fibrillation and long‐term outcomes in patients with acute myocardial infarction

Jiachen Luo,
Zhiqiang Li,
Xiaoming Qin
et al.

Abstract: AimsTo investigate the predictive value and prognostic impact of stress hyperglycemia ratio (SHR) for new‐onset atrial fibrillation (NOAF) complicating acute myocardial infarction (AMI).Materials and MethodsThis retrospective study included 2145 AMI patients without AF history between February 2014 and March 2018. SHR was calculated using fasting blood glucose (mmol/L)/[1.59*HbA1c (%)‐2.59]. The association between SHR and post‐MI NOAF was assessed with multivariable logistic regression analyses. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, individuals with cardiovascular diseases often exhibit metabolic disturbances due to unhealthy dietary and lifestyle habits, potentially exacerbating adverse cardiovascular outcomes [ 2 , 3 ]. Previous research has shown that elevated blood glucose levels upon hospital admission in patients with CVD are independently associated with poor prognosis [ 4 , 5 ]. However, hyperglycemia often arises from a combination of acute stress and chronic glucose levels and thus might not necessarily reflect an acute rise in glucose.…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with cardiovascular diseases often exhibit metabolic disturbances due to unhealthy dietary and lifestyle habits, potentially exacerbating adverse cardiovascular outcomes [ 2 , 3 ]. Previous research has shown that elevated blood glucose levels upon hospital admission in patients with CVD are independently associated with poor prognosis [ 4 , 5 ]. However, hyperglycemia often arises from a combination of acute stress and chronic glucose levels and thus might not necessarily reflect an acute rise in glucose.…”
Section: Introductionmentioning
confidence: 99%